Seasonal Dynamics of Physiological, Oxidative and Metabolic Responses in Non-lactating Nili-Ravi Buffaloes Under Hot and Humid Climate - Li, Mengwei; Hassan, Faiz-ul; Guo, Yanxia; Tang, Zhenhua; Liang, Xin; Xie, Fang; Peng, Lijuan; Yang, Chengjian (Frontiers in Veterinary Science, 2020)
Hot and humid weather exposes animals to high temperature and relative humidity that ultimately reduce their ability to disperse body heat. To avoid serious consequences of heat stress, it is imperative to understand animal physiological responses and biochemical changes during a state of altered body homeostasis across different seasons of the year. This study evaluated seasonal dynamics of physiological, oxidative, and metabolic responses of Nili-Ravi buffaloes to hot and humid climate. Twenty non-lactating multiparous buffaloes were enrolled for this 1-year study. Meteorological data were recorded twice daily to calculate temperature humidity index (THI). Physiological parameters including rectal temperature (RT), body surface temperature (BST), and respiratory rate (RR) were measured weekly. Blood samples were collected once in each season (spring, summer, autumn, and winter) to analyze biochemical and antioxidant parameters. We also measured activities of liver enzymes including alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The results revealed a significantly higher THI value (82) during summer which resulted in a significant increase in RR and BST as compared to winter. Higher oxidative stress was observed in summer owing to significantly higher malondialdehyde (MDA) content and lower levels of serum antioxidant enzymes (GPx, SOD, and CAT) as compared to other seasons. Moreover, serum cortisol was also significantly higher while adrenocorticotropic hormone (ACTH), Triiodothyronine (T3), insulin, and growth hormone contents were significantly lower in summer. Contrarily, plasma thyroxin (T4) level was higher in summer. THI showed a positive correlation with physiological responses but a negative correlation with antioxidant parameters. Our study provides practical insights on the adaptive physiology of buffaloes and has several implications regarding the alleviation of heat stress in buffaloes to enhance the efficiency of production and reproduction under tropical climate. Our study suggests the use of appropriate cooling strategies to effectively manage the non-lactating buffaloes to avoid performance losses and animal welfare issues in summer season.